CURRENT ISSUES OF PUBLIC FINANCE MANAGEMENT IN UKRAINE - V. Marhasova; I. Ruzhytskyi; N. Tkalenko; T. Shestakovska; O. Mykhailovska (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
Abstract. The article describes the approaches to defining the essence of understanding «public finance» and «public finance management» in the context of administrative and financial decentralization. A study on the current state of economic development of Ukraine is carried and the public financial management system is analyzed. The dynamics of the ratio of revenues and expenditures of the State and local budgets is shown and the national and subnational levels in the financing of public expenditures are described. The sequence of achieving a new level of welfare of the population is presented and the ways of state influence on local economic development are outlined. The content of the state’s activity on financial resources management and public importance of finances is given. Particular attention is paid to the financial capacity of UTC and the existing positive developments within the decentralization reform in Ukraine. The need to improve the management of public finances was emphasized, as it was evidenced by the size of the budget deficit. The division of budget expenditures by functional classification between the national and subnational levels is presented and the decline of financial independence of subnational budgets is witnessed. An assessment of the level of confidence in financial asset management services of territorial communities based on the calculation of the relevant index is made, and the relationship between the selected indicators (the monetary expenditures of the population; deposits of individuals in investment funds; population savings; volume of capital investments; volume of investments in Ukraine; assets of investment funds) and the level of public confidence in the management of UTC financial assets is researched.